2012
DOI: 10.1074/jbc.m112.359307
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Wild-type and Mutant Huntingtin-associated Proteins in Mouse Brains Identifies Unique Interactions and Involvement in Protein Synthesis

Abstract: Background: Differences in protein interactions between wild-type and mutant huntingtin are relevant to the disease. Results: Mutant huntingtin interacts with unique proteins and alters the subcellular context of some interactions shared with wild type. Conclusion: Mutant Huntington disease protein has loss-of-function and gain-of-function attributes. Significance: Results implicate understudied proteins and cellular/molecular processes that may contribute to the onset of the Huntington disease pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
114
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 72 publications
(83 reference statements)
13
114
0
Order By: Relevance
“…Using subcellular fractionation of brain homogenates, one study found molecular chaperones as mutant HTT interactors, in support of previous findings and highlighting the central role of these folding machineries as HTT modifiers [112]. Interestingly, components of the translational machinery were also identified as mutant HTT interacting proteins, providing a novel molecular pathway for HTT-mediated toxicity.…”
Section: Proteomic Screeningsupporting
confidence: 63%
See 1 more Smart Citation
“…Using subcellular fractionation of brain homogenates, one study found molecular chaperones as mutant HTT interactors, in support of previous findings and highlighting the central role of these folding machineries as HTT modifiers [112]. Interestingly, components of the translational machinery were also identified as mutant HTT interacting proteins, providing a novel molecular pathway for HTT-mediated toxicity.…”
Section: Proteomic Screeningsupporting
confidence: 63%
“…Recently, proteomic studies to identify HTT-associated proteins have also been done in the context of full-length HTT expressed in mouse brain, using affinity purificationmass spectrometry [112,113]. Using subcellular fractionation of brain homogenates, one study found molecular chaperones as mutant HTT interactors, in support of previous findings and highlighting the central role of these folding machineries as HTT modifiers [112].…”
Section: Proteomic Screeningmentioning
confidence: 74%
“…Recently, both WT and mHtt have been found to co-purify with several translation-related proteins and co-fractionate with ribosomes (Culver et al, 2012). Furthermore, the overexpression of Htt inhibits cap-dependent translation of a reporter mRNA in an in vitro system (Culver et al, 2012). During spermiogenesis, translational control is essential because de novo protein production is needed for the terminal steps of germ cell differentiation, which occur after transcription has ended.…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic translation initiation factor 2 (Eif2) signaling was predicted to be activated based on the upregulation of 17 ribosomal proteins. This translation activation is likely induced by knockout of Htt, as WT Htt functions with Ago2, the catalytic component of the RNAinduced-silencing complex, in a post-transcriptional gene silencing pathway, and its overexpression strongly inhibited translation in HeLa cell extracts (Savas et al, 2008;Culver et al, 2012).…”
Section: Functional Annotation Of Differentially Expressed Proteins Imentioning
confidence: 99%
“…Recently, both WT and mHtt have been found to co-purify with several translation-related proteins, and co-fractionate with ribosomes. Furthermore, Htt overexpression inhibits capdependent translation of a reporter mRNA in an in vitro system (Culver et al, 2012).…”
Section: Introductionmentioning
confidence: 99%